New insights into the genetic composition and phylogenetic relationship of wolves and dogs in the Iberian Peninsula - Pires, Ana Elisabete (2018)
This study investigates the gene pool of Portuguese autochthonous dog breeds and their wild counterpart, the Iberian wolf subspecies (Canis lupus signatus), using standard molecular markers. A combination of paternal and maternal molecular markers was used to investigate the genetic composition, genetic differentiation and genetic relationship of native Portuguese dogs and the Iberian wolf. A total of 196 unrelated dogs, including breed and village dogs from Portugal, and other dogs from Spain and North Africa, and 56 Iberian wolves (wild and captive) were analyzed for nuclear markers, namely Y chromosome SNPs, Y chromosome STR loci, autosomal STR loci, and a mitochondrial fragment of the control region I. Our data reveal new variants for the molecular markers and confirm significant genetic differentiation between Iberian wolf and native domestic dogs from Portugal. Based on our sampling, no signs of recent introgression between the two subspecies were detected. Y chromosome data do not reveal genetic differentiation among the analyzed dog breeds, suggesting they share the same patrilineal origin. Moreover, the genetic distinctiveness of the Iberian wolf from other wolf populations is further confirmed with the description of new mtDNA variants for this endemism. Our research also discloses new molecular markers for wolf and dog subspecies assignment, which might become particularly relevant in the case of forensic or noninvasive genetic studies. The Iberian wolf represents a relic of the once widespread wolf population in Europe and our study reveals that it is a reservoir of unique genetic diversity of the grey wolf, Canis lupus. These results stress the need for conservation plans that will guarantee the sustainability of this threatened top predator in Iberia.